NEWS CONSUMPTION ACROSS CONVENTIONAL MASS MEDIA AND THE INTERNET - Udi Rusadi (Jurnal Penelitian dan Pengembangan Komunikasi dan Informatika, 2014)
The development of communication and information technology has provided the audience a new alternative in news consumption, which is not only limited to conventional media e.g. newspaper, television and radio but also includes the internet based media. In order to access the mentioned internet based media, one needs the opportunity and capability to access the internet. The objective of this research is to describe the patterns of the society in terms of consuming news from conventional media and the internet, as seen from their different level of digital literacies. This research was being held with the perspective of post positivistic, using qualitative method through in-depth interviews with respondents categorized in the digital native, settler and immigrant. The result shows that the digital native society consumes more media based internet whilst the digital settler and immigrant, compared to the digital native, still intensely access the conventional media in striking comparison to the internet. The cross news consumption in the media is done as a complement for each other and to assure the truth of a matter. The pattern in news consuming is still influenced by their background and the environment they belong to. Keywords: News, Consumption, Conventional Media, Internet, Digital Literacy